Ferulic Acid From Plant Biomass: A Phytochemical With Promising Antiviral Properties - Antonopoulou, Io; Sapountzaki, Eleftheria; Rova, Ulrika; Christakopoulos, Paul (Frontiers in Nutrition, 2022)
Plant biomass is a magnificent renewable resource for phytochemicals that carry bioactive properties. Ferulic acid (FA) is a hydroxycinnamic acid that is found widespread in plant cell walls, mainly esterified to polysaccharides. It is well known of its strong antioxidant activity, together with numerous properties, such as antimicrobial, anti-inflammatory and neuroprotective effects. This review article provides insights into the potential for valorization of FA as a potent antiviral agent. Its pharmacokinetic properties (absorption, metabolism, distribution and excretion) and the proposed mechanisms that are purported to provide antiviral activity are presented. Novel strategies on extraction and derivatization routes, for enhancing even further the antiviral activity of FA and potentially favor its metabolism, distribution and residence time in the human body, are discussed. These routes may lead to novel high-added value biorefinery pathways to utilize plant biomass towards the production of nutraceuticals as functional foods with attractive bioactive properties, such as enhancing immunity towards viral infections.